2020
DOI: 10.5144/0256-4947.2020.449
|View full text |Cite
|
Sign up to set email alerts
|

The association of diabetes with ischemic stroke and transient ischemic attacks in a tertiary center in Saudi Arabia

Abstract: BACKGROUND: Diabetes mellitus increases stroke risk 1.5 to 3 fold, particularly ischemic stroke. There is limited literature on the impact of diabetes on stroke patients in Saudi Arabia. OBJECTIVES: Determine the association of diabetes on the presentation, subtypes, in-hospital complications and outcomes of ischemic stroke and transient ischemic attacks (TIA). DESIGN: IRB approved, retrospective chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…One potential explanation would be that patients who have diabetes might present symptoms congruent with those of stroke, thus they or their caregivers might have interfered based on hypoglycemia and not stroke and this can lead to a misperception and neglection of the seriousness of the condition instead of immediately moving to the ED. This result is consistent with a study done by Homoud et al Where a significant majority of the non-diabetic stroke patients presented to the ED within 3 hours of symptom onset (P = 0.003), whereas almost 38% of diabetic stroke patients presented after 24 hours of symptom onset [31].…”
Section: Discussionsupporting
confidence: 93%
“…One potential explanation would be that patients who have diabetes might present symptoms congruent with those of stroke, thus they or their caregivers might have interfered based on hypoglycemia and not stroke and this can lead to a misperception and neglection of the seriousness of the condition instead of immediately moving to the ED. This result is consistent with a study done by Homoud et al Where a significant majority of the non-diabetic stroke patients presented to the ED within 3 hours of symptom onset (P = 0.003), whereas almost 38% of diabetic stroke patients presented after 24 hours of symptom onset [31].…”
Section: Discussionsupporting
confidence: 93%
“…11,23 Recently published studies focusing the population from SA reported the prevalence of large artery disease subtype as 26% 24 and 52.6% of all admitted AIS patients. 10 However, none of the authors of extant studies examined and described ICAD as a separate category in detail. 10,24 With respect to the sample characteristics, male preponderance in our study is in agreement with the sample compositions in studies conducted in India 25 and China.…”
Section: Discussionmentioning
confidence: 99%
“…Despite gaining worldwide attention owing to recent advancements in management, literature focusing on ICAD in the Saudi Arabian (SA) context is scarce and insufficient. Nonetheless, evidence gathered from SA indicates that large artery disease (LAD) is common among AIS patients 9,10. As the real burden and clinico-radiological spectrum of ICAD have never been studied in SA, this gap in pertinent literature prompted us to identify the prevalence of ICAD-related stroke and describe its demographic, clinical, and radiologic characteristics in patients presenting to our center.…”
mentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disorder that negatively affects the function of different organs, including the salivary glands. 7 , 9 , 31 Alterations in the salivary glands can result in a decrease in saliva, which leads to devastating consequences, such as increased susceptibility to dental caries and periodontal diseases. The present study revealed a significantly lower salivary flow in diabetic patients compared to healthy controls (we can consider that the mixtures of both types of diabetes inflated these differences).…”
Section: Discussionmentioning
confidence: 99%